Enhancements in Hydrogen Storage Properties of Magnesium Hydride Supported by Carbon Fiber: Effect of C–H Interactions - Quan Yang; Xiansong Jia; Zhikang Qin; Xiaoli Ding; Yongtao Li (Inorganics)
Carbon-based materials with excellent catalytic activity provide new ideas for the development of magnesium-based hydrogen storage. C-H bonding interactions may play a key role in performance improvement. In this work, we comprehensively compare the magnesium-carbon cloth composites (CC) prepared by method of dry ball milling and wet impregnation. The results were that the hydrogen release activation energy (Ea) of MgH2@CC composites prepared by wet immersion method was 175.1 ± 19.5 kJ·mol−1, which was lower than that of pure MgH2 (Ea = 213.9 ± 6.4 kJ·mol−1), and the activation energy of MgH2-CC composites prepared by ball milling method was 137.3 ± 8.7 kJ·mol−1, which provided better results. The kinetic enhancement should be attributed to C-H interactions. The presence of carbon carriers and electron transfer to reduce the activation energy of Mg-H bond fracture. These results will provide further insights into the promotion of hydrogen ab-/desorption from metal hydrides.